Hand instrumentation provides improved tissue response over ultrasonic scaler and substantiates safe dental practice: An in vivo study in rats - de Almeida, Juliano Milanezi [UNESP]; de Araujo, Nathália Januario [UNESP]; Matheus, Henrique Rinaldi [UNESP]; de Abreu Furquim, Elisa Mara [UNESP]; Piovezan, Bianca Rafaeli [UNESP]; Fiorin, Luiz Guilherme [UNESP]; Ervolino, Edilson [UNESP] (Public Library of Science (PLoS), 2023)
Objective The aim of this study was to evaluate the effectiveness of hand debridement (HD) versus ultrasonic dental scaler (UDS) for the treatment of experimental periodontitis (EP) in rats. Material and methods Thirty 3-month-old male rats were used. EP was induced around the mandibular first molars (right and left). Seven days after induction, the treatments with either HD (n = 30) or UDS (n = 30) were randomly performed in each molar. Euthanasia were performed at 7, 15, and 30 days after treatment. Histometric (percentage of bone in the furcation [PBF]), histopathological, and immunohistochemical (for detection of tartrate-resistant acid phosphatase [TRAP] and osteocalcin [OCN]). Parametric data (PBF and TRAP) was analyzed by One-way ANOVA followed by Tukey's post-test. OCN was analyzed by Kruskal-Wallis followed by Student-Newman-Keuls post-test. The level of significance was 5%. Results Group HD presented higher PBF and lower TRAP-immunolabeling at 30 days as compared with UDS in the same period (p≤0.05). Group HD presented higher OCN immunolabeling at 30 days as compared with 7 and 15 days (p≤0.05). Persistent and exacerbated inflammatory process was observed in some specimens from group UDS at 30 days, as well as the bone trabeculae presented irregular contour, surrounded by many active osteoclasts. Conclusion Nonsurgical periodontal therapy with HD resulted in higher PBF and lower expression of TRAP as compared with UDS. Also, HD increased the expression of OCN over time.